Synthesis and Characterization of Macrocyclic Zinc(II) Complexes Containing Schiff Base - KEYPOUR, HASSAN; AZIZZADEH ARAEY, FARZANEH (Asian Journal of Chemistry, 2010)
An anthracene fragment was appended through a methylene group to the scorpionands ethylamine side chain to give macrocyclic systems L1 and L2 with a flexible pendant-arm as a potentially versatile fluoresecent system. Zn(II) complexes of [ZnL1Cl]2+ and [ZnL2Cl]2+ have been prepared by the direct reaction of performed ligand (L1 and L2) with Zn2+ ion.